Cytoreductive and Palliative Radical Prostatectomy, Extended Lymphadenectomy and Bilateral Orchiectomy in Advanced Prostate Cancer with Oligo and Widespread Bone Metastases: Result of a Feasibility, Our Initial Experience - Simforoosh, Nasser; Dadpour, Mehdi; Mofid, Bahram (Urology Journal, 2019)
purpose: to evaluate the feasibility of cytoreductive radical prostatectomy (RP), lymphadenectomy, and bilateral orchiectomy in patients with advanced prostate cancer (PCa) with oligo- and poly-metastases. Furthermore, the functional and oncological outcomes of these patients in comparison with the control group that underwent treatment only with systemic therapy (ST group) is investigated in a well-selected, prospective cohort study. Material and methods: A total of 26 patients were enrolled in CRP (cytoreductive radical prostatectomy) group and 23 patients in ST group. The patients have been followed (9 to 43 months(median:19.5)) with PSA (prostate specific antigen), whole body bone scan and other necessary imaging and laboratory tests. Functional and oncological outcomes were compared between two groups. Results: Biochemical relapse was occurred in 9 patients (34.6%) in CRP group and in 17 patients (73.9%) in ST group (p=0.01). Whole-body bone scans showed reduced metastasis volume occurred more in CRP group (p=0.003). There was no voiding dysfunction in 22 patients in CRP group post-operatively (84.6%), while in ST group trans-urethral resection of prostate or permanent Foley catheter was needed in 8 patients (34.7%) and bilateral percutaneous nephrostomy was done in one. six patients in CRP group (23%) and eight patients in ST group (34.7%) were expired because of prostate cancer and there was no difference between cancer specific survival between two groups (p=0.975). Conclusion: Although surgery doesn’t improve cancer specific survival in patients with skeletal metastatic prostate cancer in the short term, but offers better local control, improves biochemical relapse-free survival, might prevent excessive interventions, reduce bone pain and metastasis.